2014
DOI: 10.1177/1932296814527818
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Perception Threshold in the Screening of Sensorimotor Distal Symmetric Polyneuropathy

Abstract: Use of the vibration perception threshold (VPT) is a simple way of detecting large-fiber dysfunction, thus identifying individuals with diabetes at risk of ulceration. 1-2Nevertheless, poor standardization of measurement limits its use in clinical practice; 3-5 furthermore, the unique normality threshold of 25 V is criticized due to the physiologic increase in VPT with age. 6 The development of devices reducing the intra-and interoperator variability in the test execution could help research and clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…We found that with increasing age the vibration perception decreases at all points of measurement. Age-dependency of vibration perception has been first reported by Pearson et al PLOS ONE [20] and has been confirmed by several other studies [2,[4][5][6][7][21][22][23][24]. However, it is not clear what causes this reduction of vibration perception [2].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We found that with increasing age the vibration perception decreases at all points of measurement. Age-dependency of vibration perception has been first reported by Pearson et al PLOS ONE [20] and has been confirmed by several other studies [2,[4][5][6][7][21][22][23][24]. However, it is not clear what causes this reduction of vibration perception [2].…”
Section: Discussionmentioning
confidence: 80%
“…Different VPT values for a biothesiometer have been described [5,7] and it appeared that in individuals without sensory disturbances VPT are not only influenced by age [5] but also by height [7]. Bloom et al already mentioned that next to a strong correlation with age, height appeared to be of influence on VPT assessed at the feet [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results correlate with the findings of a recent study that reported a reduction in the vibration thresholds of the distal part of the feet in patients with BMS [ 13 , 16 ]. When analyzed collectively, these findings indicate a hypofunction of large fibers (Aß), as is also present in other neuropathies [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 59%
“…This discrepancy may reflect the concern that the biothesiometer, the monofilament, and the tuning fork are potentially challenged by variation in the clinical examination comprising testing technique, for instance disagreements about exact pressure applied and testing anatomic site selection, furthermore, varying interpretation of the findings, for instance, if loss of the vibrotactile perception may be a normal physical finding in the very old subjects or indicates peripheral neuropathy 27,41 . Moreover, cognitively impaired patients may have difficulties understand and respond verbally to the test, and thus indicating if the perception of the monofilament, the biothesiometer, or the tuning fork is perceived.…”
Section: Discussionmentioning
confidence: 99%